Implementation Of The Problem Based Learning Model Through Articulate Storyline Learning Media To Improve Students' Learning Outcomes In The Science Subject Of Grade V At Sdn Tamansari 1 - Resti Aisyah Amini; Didit Yulian Kasdriyanto; Ribut Prastiwi Sriwijayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines the application of the Problem Based Learning model combined with the interactive learning media Articulate Storyline in the learning of Science on the subject of Harmony in Ecosystems in class V of SDN Tamansari 1. The background of this study is based on the low student learning outcomes caused by the dominance of the lecture method and the minimal use of interesting media, so that students are less actively involved in learning. The purpose of this study is to describe the application of the media and improve student learning outcomes. The study used the Classroom Action Research method which was carried out in two cycles, including the planning, implementation, observation, and reflection stages, with 17 students as subjects. The results showed a significant increase in student learning outcomes in each cycle, where the average class score increased from 50 in the pre-cycle to 71.17 in Cycle I, and reached 91.76 in Cycle II. The percentage of learning completion also increased from 17.65% to 76.47%, until finally reaching 100% in Cycle II. These findings indicate that the use of the Problem Based Learning model combined with Articulate Storyline can encourage student engagement and deepen conceptual understanding. Therefore, it can be concluded that the implementation of these learning models and media is effective in improving science students' learning outcomes.